PENERAPAN MODEL PERSEDIAAN PRODUK MUSIMAN UNTUK MEMINIMASI EFEK BULLWHIP PADA PT FNG - Irawati, Irawati; Wilrison, Januar; Hosea, Shanty Sepvia (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
PT FNG is an industry engaged in the glassware industry in Indonesia. In implementing the distribution of PT FNG often experience problems in distribution of its products. Among others, the shortage or excess stock products. Which in turn has an impact on the overall cost performance. With the existence of bullwhip effect, profits earned by the company does not reach its maximum. The method used is forecasting to predict demand for one next year as an input for analysis of inventory performance. By using the model for seasonal products, the inventory of existing demand variability can be reduced by giving large values of the optimal echelon orders so the company gets the maximum profit. This study has obtained the most proper forecasting method for glassware production, and by determining optimal Q, has given influence to conduct coordination or involvement of previous echelon to obtain maximum profits